Διερεύνηση της παρουσίας του ιού του μωσαϊκού του πεπίνο (pepino mosaic virus,PepMV) στην Κύπρο - Μάρκου, Παναγιώτα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων,Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, 2011)
Pepino mosaic virus(PepMV,Genus:Potexvirus,Family:Flexiviridae),is a new plant virus that has become a significant agronomical problem in a relatively short period of time worldwide.In Cyprus ,the virus was detected in 2009 in greenhouse tomato crops.In order to assess the degree of infection of PepMv in Cyprus, a relevant study was conducted by the Cyprus University of Technology,in collaboration with the plant protection section of the agriculture research institute.The study included the collection of samples of tomato plants,other cultivated plants and wild plants from Ammochostos,Larnaka,Lefkosia,Limassol and Paphos districts which were tested with serological and molecular tests.A total of 1707 tomato plant samples ,60 samples of other cultivated plants and 544 samples of wild plants were collected.Based on the results,PepMV was detected in greenhouse and open field tomato crops in the districts of Limassol and Larnaca.The virus was detected in individual greenhouses in Ammochostos district(Sotera),while all samples from Paphos were negative .Furthermone,the virus was detected in 37 wild plants,which belong to the families of Amaranthaceae,Chenopodiaceae,Compositae,Convolvulaceae,Malvaceae,Plantaginaceae and Solonaceae.The samples from other cultivated plants were negative.Comparing the sensitivity detection between serological and molecular testing it was found that the molecular diagnostic technigues are more sensitive than the serological test ELISA .The conventional RT-PCR and the real time rt-pcr had 100 and 1000 times more sensitivite of the molecular technigues enabled the use of simplified and reliable methods of treading plant samples,based on the application of plant homogenates in reaction solution .The molecular characterezation and phylogenetic analysis of virys isolates fron Cyprus showed that the two Cypriot isolates were identical and possessed 99% identity with the PepMv strain Chile-2(Ch2)
Keywords: Virus; Citrus trees; Ιός; Εσπεριδοειδή